TRAVELTIME APPROXIMATION FOR A REFLECTED WAVE IN A HOMOGENEOUS ANISOTROPIC ELASTIC LAYER - Zillmer M.; Kashtan B.M. (My University, 2002)
An approximation to the traveltime field is calculated for an elastic wave that propagates in a homogeneous anisotropic layer and is reflected at a plane boundary. The traveltime is approximated by a Taylor series expansion with the third derivative of the traveltime being taken into account. The coefficients of the series refer to the seismic ray, which is locally the fastest ray. Simple formulae are obtained for orthorhombic media in the crystal coordinate system, which relate the traveltimes of the reflected waves to the elastic constants of the medium. A numerical example is presented for wave propagation in orthorhombic olivine, which is a constituent of the Earth's mantle. A second example is given by an isotropic host rock with a set of parallel cracks, which is an important model for wave propagation in the Earth's crust. The elastic parameters can be determined by measuring the reflection times as a function of source-receiver offset. The approximate traveltime-distance curves are compared with traveltimes obtained from seismic ray tracing.